Farmers’ Satisfaction with Oil Palm Business Partnership Patterns - Maswadi; Erkulanus Wawan; Wanti Fitrianti (Universitas Muhammadiyah Malang, 2022)
This study aimed to explain the mechanism of the partnership pattern between PT Sumatra Jaya Agro Lestari and farmers and the level of farmers’ satisfaction with the partnership pattern run by PT. Sumatra Jaya Agro Lestari. The location of the study was determined by purposive sampling technique, and qualitative and quantitative data were used in this study. The number of respondents in this study amounted to 84 respondents, who were selected using proportional random sampling technique. The analytical tools used in this research were the Customer Satisfaction Index and Importance Performance Analysis. The results showed that the partnership pattern had 80:20 provisions in which 80% of the total land was cultivated by the company and 20% of the total land was cultivated by the community, and the partnership activities could run well. The results of CSI analysis showed that the obtained 49.9% value indicated the “quite satisfied” criteria. Meanwhile, the attributes in the partnership to be maintained were marketing of crops, Technical Guidance, and Partnership Control Book. The company must also improve the service attributes of the partnership, the main priorities of which are: Response to Complaints and Responsibilities; fewer major priorities, namely (Rights and Obligations) Plantation Development, Obtaining Transparent Information, Provision of Saprodi (Production Facilities), and Price Agreements.